Growth and macronutrients in Cenchrus purpureus cv. Taiwan with and without fertilization in Veracruz - Vinay-Vadillo, Julio César; Herrera-sotero, Monica Yazmín; Juárez-Jiménez, Aguedo; Montero-Lagunes, Maribel; Villegas-Aparicio, Yuri; Enriquez-Quiroz, Javier Francisco; Bolaños-Aguilar, Eduardo Daniel; Mendoza-Pedroza, Sergio Iban (Ecosistemas y Recursos Agropecuarios, 2021)
The objective was to determine the growth curves and rates of nitrogen, phosphorus, potassium, as well as their extraction and efficiency from the cultivar Taiwan with and without fertilizing in Veracruz. The experiment carried out during the rainy season in Aw2, tropical sub-humid climate. Seven fertilized (141-43-20) and unfertilized plots of Cenchrus purpureus cv Taiwan were established. The samplings carried out every 21 days until 168 days of regrowth age. The forage samples were determined Dry Matter (DM), N, P, K, Ca, Mg and S. The data adjusted to linear and non-linear models. They evaluated with goodness of fit indicators to estimate the parameters. In addition, the apparent efficiency of N, P, K was calculated. The parameters analyzed in a completely randomized design, with two treatments, fertilized (four repetitions) and unfertilized (three repetitions). The means compared with Tukey’s test with Minitab v17 software. The growth parameters, NPK curves, and NPK extraction in the fertilized and unfertilized treatment show that to produce 6000 kg DM ha-1 at 77 days of growth, 186 kg N, 27 kg P2O5, 279 kg K2O, 75 kg Ca, 22 kg Mg and 3 kg of S ha-1 are required. While without fertilizing, it produced 3000 kg DM ha-1, and extracted a third of the nutrients extracted by the fertilized treatment. It concluded that the nutrient extraction rates were higher in the fertilized treatment.